Pengembangan Media Permainan Media Ular Tangga Digital pada Mata Pelajaran IPAS dI SD - Connyta Elvadola; Try Indiastuti Kurniasih; Ridho Agung Juwantara; Endah Rahmawati (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This research is a development research using the ADDIE model. This ADDIE model has 5 stages, namely 1)Analysis, 2)Design, 3)Development,4) Implementation, and 5) Evaluation. This model can be used for various shapes product development in learning activities such as models, strategies learning, learning methods, media and teaching materials. The researcher developed a traditional snakes and ladders game media product into an Android-based snakes and ladders game media. The purpose of this study was to improve student learning outcomes in the fifth grade science subject at SD Negeri 5 Jatimulyo.